PENGEMBANGAN E-LKPD BERBASIS ETNOMATEMATIKA CANDI PRAMBANAN PENDEKATAN CTL PENGEMBANGAN GEOMETRI BANGUN RUANG - Mujtahidah, Siti Agustina; Mauliza, Dara; Mawarsari, Venissa Dian (Journal of Lesson Study in Teacher Education, 2025)
Students experience difficulties in understanding geometric geometry because the learning media used are still monotonous and do not integrate local cultural elements or digital technology. Contextual learning through ethnomathematics, particularly the utilization of the structure and ornamentation of Prambanan Temple, can help students build a more meaningful understanding (Rizki & Khaerunnisa, 2022; Yuliani et al., 2023). Contextual Teaching and Learning (CTL)-based e-LKPD is the right solution because it can encourage interactive, relevant, and student-centered learning activities (Sari & Ningsih, 2021). This study aims to design and develop an e-LKPD containing ethnomathematics of Prambanan Temple. Validity testing was conducted by two mathematics education lecturers and one junior high school teacher, with assessments covering aspects of presentation, language, appearance, media implementation, and suitability of the material with the CTL approach (Rahmawati & Putra, 2023). The validity results show that the developed E-LKPD obtained an average score of 90.3%, which is categorized as very valid and suitable for use in mathematics learning. Thus, this CTL-based E-LKPD containing ethnomathematics of Prambanan Temple can be an alternative innovative and contextual learning media for the geometry of flat shapes material for grade VIII junior high school